Studi Kasus Kemampuan Berpikir Kritis Isu Lingkungan Lokal Mahasiswa Pendidikan IPA Semester 6 Jurusan Biologi UNIMED - Indriani Laurensia Br Tarigan; Lisnawaty Simatupang (Lembaga Riset dan Inovasi Almatani, 2026)
This study aims to profile the conceptual understanding levels and detect misconceptions regarding the eutrophication of Lake Toba among pre-service biology teachers. A Two-Tier Diagnostic Test was developed to measure four critical thinking indicators: interpretation, analysis, inference, and evaluation. Student responses were classified into four cognitive states: Concept Understanding (PK), Misconception (MK), Partial Concept (KP), and No Understanding (TP). The results revealed a linear degradation of scientific reasoning as the complexity of critical thinking indicators increased. The percentage of students with full Concept Understanding (PK) dropped drastically from interpretation (35%), analysis (19%), and inference (11%), leaving only 4% at the evaluation indicator. Conversely, the